HIV Testing and Access in Palembang, South Sumatra, Indonesia During the 2021 COVID-19 Pandemic - Najmah Najmah; Namirah Adelliani; Mawaddah Dyah Popita; Ajeng Fathia Nurqanita; Amrina Rosyada; Iwan Stia Budi; Fenty Aprina; Yulyana Kusuma Dewi; Yudhi Setiawan; Sari Andajani (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
HIV testing is one of the most effective strategies for accelerating access to prevention and treatment services, supporting efforts to end the AIDS epidemic by 2030 through the 95-95-95 targets. This study describes the socio-demographic characteristics and spatial distribution of HIV cases and screening among key and general populations in Palembang City in 2021. Data were extracted from the HIV/AIDS Information System and analyzed using descriptive and ecological spatial analysis within the key and general populations. Findings indicate the rates of HIV are 4.2 per 100 among Men having Sex with Men (MSM) and 7.8 per 100 transgender individuals accessing HIV testing. Among women and pregnant women, rates were zero and 1.04 %, respectively, while among children (0-19 years old), the rate was nearly 2 per 100 children. A higher level of HIV testing in health facilities was correlated with increased detection of HIV cases. Among low-risk groups of women and children, one subdistrict, Kemuning, reported 30 HIV- positive cases in women and children – markedly higher than the 0 to 6 HIV-positive cases reported in other subdistricts. The observed disparity underscores a critical public health challenge: the potential for a hidden HIV epidemic among pregnant women in Palembang, a situation likely exacerbated by service disruptions during the COVID-19 pandemic.